Atypical resting synchrony in autism spectrum disorder - Ye, Annette X. (Hum Brain Mapp, 2014)
Autism spectrum disorder (ASD) is increasingly understood to be associated with aberrant functional brain connectivity. Few studies, however, have described such atypical neural synchrony among specific brain regions. Here, we used magnetoencephalography (MEG) to characterize alterations in functional connectivity in adolescents with ASD through source space analysis of phase synchrony. Resting‐state MEG data were collected from 16 adolescents with ASD and 15 age‐ and sex‐matched typically developing (TD) adolescents. Atlas‐guided reconstruction of neural activity at various cortical and subcortical regions was performed and inter‐regional phase synchrony was calculated in physiologically relevant frequency bands. Using a multilevel approach, we characterized atypical resting‐state synchrony within specific anatomically defined networks as well as altered network topologies at both regional and whole‐network scales. Adolescents with ASD demonstrated frequency‐dependent alterations in inter‐regional functional connectivity. Hyperconnectivity was observed among the frontal, temporal, and subcortical regions in beta and gamma frequency ranges. In contrast, parietal and occipital regions were hypoconnected to widespread brain regions in theta and alpha bands in ASD. Furthermore, we isolated a hyperconnected network in the gamma band in adolescents with ASD which encompassed orbitofrontal, subcortical, and temporal regions implicated in social cognition. Results from graph analyses confirmed that frequency‐dependent alterations of network topologies exist at both global and local levels. We present the first source‐space investigation of oscillatory phase synchrony in resting‐state MEG in ASD. This work provides evidence of atypical connectivity at physiologically relevant time scales and indicates that alterations of functional connectivity in adolescents with ASD are frequency dependent and region dependent. Hum Brain Mapp 35:6049–6066, 2014. © 2014 Wiley Periodicals, Inc.